2010
DOI: 10.1248/bpb.33.1620
|View full text |Cite
|
Sign up to set email alerts
|

3.ALPHA.,23-Isopropylidenedioxyolean-12-en-27-oic Acid, a Triterpene Isolated from Aceriphyllum rossii, Induces Apoptosis in Human Cervical Cancer HeLa Cells through Mitochondrial Dysfunction and Endoplasmic Reticulum Stress

Abstract: Despite of the widespread use of the Papanicolaou smear and HPV (human papollomavirus) vaccine, cervical cancer remains the most common cancer in women under 45 years of age in developing countries. Furthermore, almost half of all women with invasive cervical cancer are diagnosed at a late stage. Accordingly, there is an urgent need to identify an agent that can be used alone or in combination with a conventional anti-cancer drug like cisplatin, to improve the prognosis of this disease. 1)Apoptosis, a morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…It is reported that the overexpression of calpains promotes the cleavage of Bid, which in turn modulates Bax and activates caspase-3. There is also evidence to suggest that activation of caspase-4 requires calpains ( 38 40 ). The aforementioned results suggest that calcium signaling involves two apoptotic pathways: i) Calcium ion entry into the mitochondria, which induces calcium disorder in he mitochondria and leads to mitochondria-mediated apoptosis; and ii) calcium signaling in the cytosol activates calcium-dependent proteases and results in the expression of ER stress-associated apoptotic proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that the overexpression of calpains promotes the cleavage of Bid, which in turn modulates Bax and activates caspase-3. There is also evidence to suggest that activation of caspase-4 requires calpains ( 38 40 ). The aforementioned results suggest that calcium signaling involves two apoptotic pathways: i) Calcium ion entry into the mitochondria, which induces calcium disorder in he mitochondria and leads to mitochondria-mediated apoptosis; and ii) calcium signaling in the cytosol activates calcium-dependent proteases and results in the expression of ER stress-associated apoptotic proteins.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate this hypothesis, the calcium chelating agent, BAPTA/AM, was used to block free Ca 2+ in the cytoplasm. Won et al reported that apoptosis induced by 3α,23-isopropylidenedioxyolean-12-en-27-oic acid was substantially reduced following combined treatment with BAPTA/AM in HeLa cells ( 40 ). In the present study, HeLa cells were treated with cisplatin combined with BAPTA/AM.…”
Section: Discussionmentioning
confidence: 99%
“…There are three apoptotic pathways: cell surface death receptors‐Caspase‐8‐Caspase‐3 ; mitochondria/MMP‐Cyt C‐Caspase‐9‐Caspase‐3 ; endoplasmic reticulum/Ca 2+ ‐Caspase‐12‐Caspase‐3 . The three apoptotic cascades converge on the activation of caspase‐3, which results in the cleavage of intracellular poly (ADP ribose) polymerase (PARP‐1) and the activation of DNase, leading to DNA fragmentation . Bcl‐2 family members play important roles in mitochondria‐dependent activation of caspase cascades .…”
Section: Discussionmentioning
confidence: 99%
“…Notably, viscumTT and viscum treatment concurrently displayed a decrease of EIF2AK3, whereas TT treatment showed a slight upregulation matching ER stress. Others demonstrated the induction of apoptosis by ER stress in HeLa cells after treatment with an oleanolic acid derivative [73]. Proteomic investigation of betulinic acid-induced apoptosis in HeLa cells also displayed the induction of ER stress [74].…”
Section: Discussionmentioning
confidence: 99%